Schaum's Strength of Materials Problem 6.24 - Pitarresi, James M. (McGraw-Hill's AccessEngineering., 2013)
This video demonstrates how to use singularity functions to write the shear and bending moment equations for the simply-supported beam with a centered distributed load.